IMPLEMENTATION OF SMART CITY POLICY TO ADVANCE THE ECONOMY IN BANDA ACEH CITY (CASE STUDY: URT CINTA KASIH HOUSING, PANTERIEK VILLAGE) ACEH PROVINCE - Ridha Mafdhul; Muttaqin Hasan; Safwan Safwan (Prodi Magister Teknik Sipil Unsyiah, 2021)
A smart city is an urban development and management strategy designed to assist various activities and provide easy information to the public. Since 2017, the Banda Aceh City Government has adopted an electronic-based planning system to encourage policymakers and create a transparent and participatory bureaucracy. In addition, Banda Aceh is a trading and service city that has significant micro-economic potential with the growth of the MSME sector reaching 25% per year and is the backbone of the city's economy (Bappeda Banda Aceh City, 2019). This potential must be encouraged by the use of technology and information as well as digital means to achieve better economies of scale. Therefore, the implementation of the smart city in Banda Aceh is expected to continue to grow to improve the economy and quality of life of the community. The focus of the research is the implementation of a smart city in Banda Aceh City and the role of the smart economy in improving the community's economy, especially HBE in Panteriek Village. By using a qualitative method involving the government, 23 household business actors, and digital marketing practitioners, the results show that the development and management of smart cities have been carried out optimally from a government perspective. However, the implementation is still not optimal due to the limited human resources from the government and users. On the other hand, the growth of business groups and the support of internet facilities provide great opportunities for the development of a smart economy by optimizing financial support to develop a marketplace to improve the economy and people's welfare.